(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The purpose of present study was to examine the relationship between the teacher’s self efficacy and Professional Responsibility. This research paper is based on a study conducted to analyze the relationship between teacher’s self-efficacy and Professional Responsibility. The sample size of the study was 150 Teachers. Random sampling technique was used to select the representative sample for the study from the population. Regression analysis was applied to find out the cause and effect relationship between teacher’s self-efficacy and Professional Responsibility. The major findings of the study indicate that there is a significant relationship between Teacher’s Self Efficacy and Professional Responsibility.